2020
DOI: 10.1111/jcpe.13337
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reported illness perception and oral health‐related quality of life predict adherence to initial periodontal treatment

Abstract: Aim To investigate the impact of periodontal disease perception and oral health‐related quality of life (OHRQoL), towards the initial periodontal treatment adherence (IPTA). Material and Methods This prospective study included 571 patients (274 males and 297 females, mean age 63.1 ± 14.5) with periodontal disease, from the Study of Periodontal Health in Almada‐Seixal (SoPHiAS). We assessed the potential connections, between sociodemographic characteristics, oral hygiene behaviours, periodontal measures, the Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 47 publications
0
14
0
1
Order By: Relevance
“…Another limitation is the patients’ inability to report, precisely, the cause of tooth loss. Recent studies in this regional area, but also at a national level, have demonstrated the serious ignorance regarding oral health, its consequences and oral hygiene habits [ 63 , 64 , 65 , 66 , 67 , 68 ]. Thus, it would be very risky to consider self-reported data regarding the cause of tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the patients’ inability to report, precisely, the cause of tooth loss. Recent studies in this regional area, but also at a national level, have demonstrated the serious ignorance regarding oral health, its consequences and oral hygiene habits [ 63 , 64 , 65 , 66 , 67 , 68 ]. Thus, it would be very risky to consider self-reported data regarding the cause of tooth loss.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, PD has been linked to other factors such as oral health behaviors and psychological characteristics [ 20 , 68 , 69 ]. Nevertheless, no studies have assessed OHRQoL, periodontal status and oral hygiene habits among women attending a fertility clinic.…”
Section: Discussionmentioning
confidence: 99%
“…With the use of this subjective measure, an individual's health status and functional capacity can be determined [6]. Self-reported tools have recently been used in Spain [7,8] and in neighboring countries such as Portugal [9,10] to assess the prevalence of periodontitis in the general population. However, perceptions can vary depending on social groups [11].…”
Section: Introductionmentioning
confidence: 99%